Temperature-dependent thermal behavior of impurity hydrogen trapped in vacancy-type defects in single crystal ZnO. (October 2018) - Shimizu, H.; Sato, W.; Mihara, M.; Fujisawa, T.; Fukuda, M.; Matsuta, K.
Abstract: Interacting nature between impurity hydrogen atoms and vacancy-type defects in single crystal ZnO was investigated by means of positron annihilation lifetime spectroscopy. In order to clarify the observation of their thermal behavior, the sample was implanted with 1 H + using an electrostatic accelerator. After the implantation, the positron lifetime became shorter, which suggests that the hydrogen atoms were captured by zinc vacancies ( V Zn ) to form vacancy-hydrogen complexes ( V Zn + n H). The complexes decompose by heat treatment: most of the hydrogen atoms gradually dissociate from V Zn + n H in the temperature range 393–773 K. It was also suggested that large vacancy clusters were formed by the agglomeration of smaller clusters during the process of stepwise isochronal annealings at temperatures from 773 to 1073 K, and their decomposition took place at 1173–1373 K. Temperature-dependent thermal behaviors of hydrogen atoms and vacancy-type defects in ZnO are discussed. Highlights: Thermal behavior of V Zn + n H in single crystal ZnO was investigated by means of PALS. The V Zn + n H complexes were formed by proton beam implantation. The hydrogen atoms gradually dissociate from V Zn + n H at the temp. range of 393–773 K. Thermal dissociation process of the V Zn + n H was observed for the first time.